| x+2[7x+(-2+3x)]=14-3(7-x) | | (x^2-2x-3)sqrt(x-2)=0 | | z=5-0.5z+y | | (X^2-2x-3)sqrtx-2=0 | | 1.2x^2-0.7x-1=0 | | (x+3)(2x+1)=7 | | 2(4m+15)=70 | | P/9=-11 | | t(4t-3)-(4t-3)(t-3)= | | cosx=(-1) | | (18+16)+6N=4 | | 2(y-3)=5+4y | | 2x-3(-1-x)=3+5(5-5x)+2(x+12-2) | | -5(7r-6)=-75 | | 2(x^2+20)=21x | | 2(x-3)=5(2x-4) | | -3w+84=51 | | 4(3t-2)=64 | | 5r+15=5 | | v=-3(2u-w) | | 5(4y+2)=-50 | | 4y=y-15 | | (2x)2+4(2x)-32=0 | | X*Y=35 | | x*Y=34 | | 3x+5=2x+30 | | 57*ln(x+1)=20 | | 80-23*ln(x+1)=20 | | 8/-2=-7 | | 4-[7-3(5-2x)]=4x+2(7x-1) | | 2t=2(s-r) |

| 18-3y=6-2y | | 9=10+6 | | 5(3+y)-18=37 | | 4a+2b+3=3 | | x/3=1.5 | | 51-3(7x+2)=4-[3-(2-x)] | | (4x^3-6x^2-12x-18)/(x^2-x-12)^2 | | lnX=2ln(x-2) | | -5/2-2/7 | | x^2=y+x | | -2.3y-9.34=6.3 | | -8=-2k | | 3-3y=7 | | X^2-4X-8y-26=0 | | 112+7x=180 | | (r^4)+16=0 | | 3x/5=1/6 | | 3(0)-4y=-12 | | x(3x+4)=15 | | x^-2(x^11/9) | | a^3-7a+6=0 | | (1-i)z^3-2iz-2=0 | | 3x-4=120 | | z^3-iz^2-2iz-2=0 | | 3(n+2)+7=22 | | 2/3p=-16 | | 6(2x-3)+15=5(x+5) | | Xsquared-6x+9=0 | | 2-1.5x=5 | | 4n^4p+x^2-5x+2=0 | | 3w-w^2=2 | | 2x-3(x-2)=4x+1 | | 5(x-2)+(-9)=-7 | | 7x+9=2x+13 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions